CULTURE IN GLOCALIZATION PROCESS: A STUDY OF INDONESIAN NEWSPAPERS - Fikry Zahria Emeraldien (President University, 2018)
Abstract - The present study examines the construction of global to the local content in Indonesian newspapers after New Order Era, Indonesia former President Suharto’s regime that was ended in 1998. In the so-called Reform Era, Indonesia entered a new phase of democratization which brings democracy towards newspapers and other media. Compared to the New Order Era, Indonesian newspapers currently have more variation in term of content, especially for entertainment. After employing a content analysis, Indonesian newspapers, which are Kompas and Jawa Pos, through their cross-cultural news in the entertainment section, are proved become more open to the other cultures. They have transformed from dominantly homogeneous -in 2004- to hybrid -in 2014- within glocalization, a perspective that can see micro-sociological phenomenon. This notion proves that glocalization does proceed, rather than keep constant, depending on the different cultural systems and structures, as well as the degree of local perception of glocalization.Keywords: Glocalization, globalization, pop culture, Indonesia Reform Era, crossculture